Influence Of A Work Culture Of Berakhlak, Motivation, Organizational Support And Job Satisfaction On Employee Performance - Dian Sari Anggraini; Yuniorita Indah Handayani; Muhammad Firdaus (LPPM Institut Teknologi dan Sains Mandala, 2024)
This research aims to examine the influence of a work culture of BerAKHLAK, motivation, organizational support, and job satisfaction on employee performance at Bondowoso Regency. The population in this study was 181 employees and the sample was 125 employees selected using the purposive sampling method. The research method used is a survey method using a questionnaire as a data collection instrument. The collected data was analyzed using multiple linear regression techniques. The research results show that work culture of BerAKHLAK, motivation, organizational support, and job satisfaction have a significant influence on employee performance. work culture of BerAKHLAK and organizational support have a significant positive impact on employee performance, while motivation has a significant positive influence on employee performance. Job satisfaction also has a significant positive influence on employee performance. These findings show the importance of implementing a fair work system with BerAKHLAK to improve employee performance. It is also necessary to pay attention to strong organizational support to encourage better performance. This research contributes to the development of theory and practice of human resource management in the agricultural and food security sectors. The practical implication of this research is the importance of the Bondowoso Regency government through the Bondowoso Regency Environmental Service to encourage the implementation of a BerAKHLAK work culture, strengthen organizational support, and increase employee job satisfaction to improve their performance.